2013
DOI: 10.1097/aln.0b013e318295a27b
|View full text |Cite
|
Sign up to set email alerts
|

Phasic Genioglossus and Palatoglossus Muscle Activity during Recovery from Sevoflurane Anesthesia

Abstract: Genioglossus and palatoglossus activity increases during recovery from sevoflurane anesthesia in a dose-dependent manner over the clinical range of sevoflurane concentrations in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Airway endoscopy in children has also demonstrated that halothane causes dynamic changes of the upper airway and laryngeal inlet . Sevoflurane has dose‐dependent effects, with decreasing phasic inspiratory genioglossus activity seen with increasing depth of sevoflurane anesthesia and no difference in tonic activity . Sevoflurane can also decrease airway patency, especially during inspiration .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Airway endoscopy in children has also demonstrated that halothane causes dynamic changes of the upper airway and laryngeal inlet . Sevoflurane has dose‐dependent effects, with decreasing phasic inspiratory genioglossus activity seen with increasing depth of sevoflurane anesthesia and no difference in tonic activity . Sevoflurane can also decrease airway patency, especially during inspiration .…”
Section: Resultsmentioning
confidence: 99%
“…44 Sevoflurane has dose-dependent effects, with decreasing phasic inspiratory genioglossus activity seen with increasing depth of sevoflurane anesthesia and no difference in tonic activity. 45 Sevoflurane can also decrease airway patency, especially during inspiration. [46][47][48] In a study using both sevoflurane and nitrous oxide for induction and propofol for anesthesia maintenance, the greatest narrowing was seen at the soft palate level, and the airway dimensions changed when sedated versus awake.…”
Section: Resultsmentioning
confidence: 99%
“…56 A study of sevoflurane demonstrated a dose-dependent effect on 2 of the major upper airway dilator muscles, the genioglossus and palatoglossus. 59 Litman et al reported decreased pharyngeal dilator muscle activity with halothane and sevoflurane, with sevoflurane causing relatively more upper airway obstruction. 60 Due to these concerns, the development group agreed that efforts should be made to minimize inhalation agent usage during pediatric DISE.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also suggested exaggerated upper airway collapse with inhalational agents 56 . A study of sevoflurane demonstrated a dose‐dependent effect on 2 of the major upper airway dilator muscles, the genioglossus and palatoglossus 59 . Litman et al reported decreased pharyngeal dilator muscle activity with halothane and sevoflurane, with sevoflurane causing relatively more upper airway obstruction 60 .…”
Section: Discussionmentioning
confidence: 99%